2018
DOI: 10.5005/jp-journals-10028-1284
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Alexithymia, Quality of Life, and Facial Emotion Recognition Abilities in Somatoform Disorders

Abstract: Aim: To assess alexithymia and quality of life among patients of somatoform disorders (SFD) compared with healthy control subjects and to assess the association between alexithymia and facial emotion recognition ability and its influence on quality of life within diagnostic subgroups of SFD.Materials and methods: Forty-three patients diagnosed to have SFD (International Classification of Diseases (ICD)-10) were assessed on the World Health Organization (WHO) SFD symptom checklist, Toronto Alexithymia Scale-26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Facial expressions can represent our emotional states and affect the generation and regulation of emotional states and behaviors in response to environmental signals [36]. FER is impaired in patients with high levels of alexithymia [37][38][39][40][41][42][43]. In addition, alexithymic patients show less activity in areas of the brain involved in extracting emotional components from facial expressions and FER (amygdala, insula, inferior frontal gyrus, striatum, and middle temporal gyrus) [27,38,43].…”
Section: Introductionmentioning
confidence: 99%
“…Facial expressions can represent our emotional states and affect the generation and regulation of emotional states and behaviors in response to environmental signals [36]. FER is impaired in patients with high levels of alexithymia [37][38][39][40][41][42][43]. In addition, alexithymic patients show less activity in areas of the brain involved in extracting emotional components from facial expressions and FER (amygdala, insula, inferior frontal gyrus, striatum, and middle temporal gyrus) [27,38,43].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in line with alexithymia have been particularly popular in psychosomatic literature because high levels of alexithymia are associated with various psychosomatic illnesses ( 18 ). Many studies, there is significant relationship between alexithymia and somatization in clinical and nonclinical samples ( 20 , 21 , 22 ). Researchers found that even when physicians confirm a physical illness, anxiety or depression, all alexithymia components; including difficulty in identifying emotions, difficulty in describing emotions and externally-oriented thinking, are associated with higher somatic symptoms in the general population.…”
mentioning
confidence: 99%